A Novel Treatment Protects Chlorella at Commercial Scale from the Predatory Bacterium Vampirovibrio chlorellavorus - Ganuza, Eneko; Sellers, Charles E.; Bennett, Braden W.; Lyons, Eric M.; Carney, Laura T. (Frontiers in Microbiology, 2016)
The predatory bacterium, Vampirovibrio chlorellavorus, can destroy a Chlorella culture in just a few days, rendering an otherwise robust algal crop into a discolored suspension of empty cells. Chlorella is used as a benchmark for open pond cultivation due to its fast growth. In nature, V. chlorellavorus plays an ecological role by controlling this widespread terrestrial and freshwater microalga, but it can have devastating effects when it attacks large commercial ponds. We discovered that V. chlorellavorus was associated with the collapse of four pilot commercial-scale (130,000 L) open-pond reactors. Routine microscopy revealed the distinctive pattern of V. chlorellavorus attachment to the algal cells, followed by algal cell clumping, culture discoloration and ultimately, growth decline. The "crash" of the algal culture coincided with increasing proportions of 16s rRNA sequencing reads assigned to V. chlorellavorus. We designed a qPCR assay to anticipate an impending culture crash and developed a novel treatment to control the bacterium. We found that 1) Chlorella growth was not affected by a 15 min exposure to pH 3.5 in the presence of 0.5 g/L acetate, when titrated with hydrochloric acid and 2) this treatment had a bactericidal effect on the culture (2-log decrease in aerobic counts). Therefore, when qPCR results indicated a rise in V. chlorellavorus amplicons, we found that the pH-shock treatment prevented the crash and doubled the productive longevity of the culture. Furthermore, the treatment could be repeatedly applied to the same culture, at the beginning of at least two sequential batch cycles. In this case, the treatment was applied preventively, further increasing the longevity of the open pond culture. In summary, the treatment reversed the infection of V. chlorellavorus as confirmed by observations of bacterial attachment to Chlorella cells and by detection of V. chlorellavorus by 16s rRNA sequencing and qPCR assay. The pH-shock treatment is highly selective against prokaryotes, and it is a cost-effective treatment that can be used throughout the scale up and production process. To our knowledge, the treatment described here is the first effective control of V. chlorellavorus and will be an important tool for the microalgal industry and biofuel research.